2012
DOI: 10.1074/jbc.m112.366450
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Hutchinson-Gilford Progeria Mutation during Osteoblast Development Results in Loss of Osteocytes, Irregular Mineralization, and Poor Biomechanical Properties

Abstract: Background: Tissue-specific mouse model for Hutchinson-Gilford progeria syndrome (HGPS). Results: Dysfunctional osteoblast maturation and impacts DNA damage and Wnt signaling, which lead to abnormal bone mineralization and impaired skeletal and dental structures. Conclusion: Resemble clinical features of HGPS and normal bone aging.Significance: Provides insights to the molecular mechanisms of HGPS and will be useful to further elucidate the processes that contribute to general bone aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
62
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 50 publications
(56 reference statements)
8
62
1
Order By: Relevance
“…Bitransgenic mice were generated as previously described (22). Genotyping was performed according to published protocols (23, 24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bitransgenic mice were generated as previously described (22). Genotyping was performed according to published protocols (23, 24).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used a mouse model with the osteoblast‐and osteocyte‐specific inducible transgenic expression of the most common HGPS mutation (22). These mice develop a bone phenotype that closely resembles the bone abnormalities of individuals who are affected by HGPS and that is reminiscent to aging bone changes (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, lymphocytes from patients with type 2 diabetes (T2D) have reduced capacity to repair ROS-induced DNA damage, and NHEJ deficiency impairs pancreatic β-cells 55,56 . Furthermore, differentiation of bone-forming osteoblasts is inhibited by DNA damage and contributes to weakened bone structure in a progeria mouse model 57 . In line with this evidence, defective NHEJ can result in osteopenia, a less severe ageing-related form of osteoporosis 58 .…”
Section: Genomic Instability In Ageing and Aadsmentioning
confidence: 99%
“…A few pieces of evidence have suggested that HGPS might be associated with defective WNT/β‐catenin signaling cascades . Stem cells isolated from Zmpste24‐/‐ mice exhibit alterations in the WNT signaling pathway .…”
Section: Introductionmentioning
confidence: 99%